2018
DOI: 10.1111/1462-2920.14498
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in patients after surgical treatment for colorectal cancer

Abstract: Summary Colorectal cancer (CRC) is a common disease worldwide that is strongly associated with the gut microbiota. However, little is known regarding the gut microbiota after surgical treatment. 16S rRNA gene sequencing was used to evaluate differences in gut microbiota among colorectal adenoma patients, CRC patients, CRC postoperative patients and healthy controls by comparing gut microbiota diversity, overall composition and taxonomic signature abundance. The gut microbiota of CRC patients, adenoma patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
1
29
0
2
Order By: Relevance
“…The community composition was calculated by the percent of community abundance according to the average of OTU abundance of each OTU with the combination of less than 1% abundance of OTUs in different elevations of two mountains. AMF community richness, evenness and diversity were expressed by the index of sobs, shannoneven and Shannon based on AMF OTU level, respectively [24,25]. Canonical correspondence analysis (CCA) was employed for exploring the relationships between AMF community and environmental variables at the level of p ≤ 0.05 and p ≤ 0.01, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The community composition was calculated by the percent of community abundance according to the average of OTU abundance of each OTU with the combination of less than 1% abundance of OTUs in different elevations of two mountains. AMF community richness, evenness and diversity were expressed by the index of sobs, shannoneven and Shannon based on AMF OTU level, respectively [24,25]. Canonical correspondence analysis (CCA) was employed for exploring the relationships between AMF community and environmental variables at the level of p ≤ 0.05 and p ≤ 0.01, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to the exploration of noninvasive markers to predict cancer recurrence after curative treatment. 74…”
Section: Microbiota and Surgical Proceduresmentioning
confidence: 99%
“…Our previous cross-sectional study showed differences in post-operative fecal microbiota between patients with and without metachronous adenoma [18]. We wonder whether such difference could exist in the preoperational fecal samples, and if there could be relationship between pre-and postcolectomy gut microbiota profile.…”
Section: Discussionmentioning
confidence: 93%
“…As CRC develops gradually from premalignant adenomatous, accurate prediction and early detection polyp provides an opportunity to halt this process. Our previous study found that colorectal cancer patients who developed metachronous adenoma postoperatively showed distinct fecal microbiota, which can be potentially used for diagnosis for metachronous adenoma [18]. But this difference already existed before operation or formed postoperatively is still unknown.…”
Section: Introductionmentioning
confidence: 98%